Avaliação do desempenho de trocadores de calor - Gardenal, Angélica Lubaski (2016)
Heat exchangers are equipments used in most of the chemical and physical processes in a production line, becoming a constant matter of studies and updates in the engineering area. This way, this paper aimed in comparing the efficiency of two common types often used, the concentric tubes and the plate heat exchangers. To this end, an experimental planning for two input variables was done, the first one being the input temperature of the hot fluid, which was varied from 40 to 60ºC, and the second studied variable was the hot fluid flow rate, which was analyzed between 0,6 and 1,6L/min. As a result of this planning, the relation between temperature and flow rate that generated the biggest heat exchange was obtained, besides the comparison between both equipment heat exchanges, concluding which is the more effective one. For both equipments the chosen working fluids was water. Eleven experiments were made on both exchangers, and, with them, it was made possible to calculate the amount of exchanged heat and find the best efficiency of the plate heat exchanger compared to the concentric tubes one. It was also possible to obtain as a result equations that relate temperature and flux of the hot fluid within the studied zone for the best heat exchange in both equipments, with the help of the Statistica software. The experimental planning data was used to trace the response surfaces, on which it was posible to view the relationship between the independent variables as a result. Besides that, it was possible to analyze the behavior of the overall heat transfer coefficient, which, by the variation of the operation conditions for each of the exchangers, oscillated in a very similar way when calculated by the two diferente methods, which are, the logarithmic mean temperature difference and the number of transfer units methods.